Hypoxia-activated small molecule-induced gene expression - Collins, S (2018)
Hypoxia, conditions of insufficient oxygen, can occur in a wide variety of biological environments, including solid tumours, bacterial biofilms, and plants. Hypoxic tumours are associated with aggressive tumour phenotypes, increased resistance to radio- and chemotherapy, and poor patient prognosis. In biofilms, low oxygen delivery to cells causes significant reduction in bacterial growth rates, which increases resistance to antibiotics. Plants most commonly become hypoxic through flooding, which negatively impacts crop yields. Consequently, tools to study hypoxia are crucial. Hypoxia-activated prodrugs offer the ability to deliver compounds selectively to regions of hypoxia, through attachment of bioreductive groups, (e.g. 4 nitrobenzyl moiety). Oxygen-dependent nitroreductase enzymes catalyse reduction of the nitro group to form a radical nitro anion, which is re-oxidised back to the nitro group in the presence of oxygen. Under hypoxic conditions, this futile REDOX cycling cannot occur. The nitro anion radical is further reduced to form a hydroxylamine or amine; subsequent fragmentation releases the drug. This work combines the concept of hypoxia-activated prodrugs with an IPTG-inducible gene expression system in BL21 (DE3) E. coli bacteria. We hypothesised that protecting IPTG 76 with a bioreductive group would inhibit IPTG-induced expression. Only under hypoxic conditions will reduction of the bioreductive group, release of IPTG 76 and induction of gene expression occur. First, a hypoxia-activated resorufin-based fluorophore was employed to determine whether hypoxia-dependent bioreduction of a nitroaryl group would take place in bacteria using the BL21 (DE3) strain of E. coli. Then a range of derivatives of IPTG, protected with a bioreductive group were synthesised and analysed for their ability to undergo reduction and fragmentation to release IPTG 76. Using, sfGFP as a reporter gene, these were then tested for their ability to induce hypoxia-dependent gene expression in BL21 (DE3) E. coli. Through fluorescence and western blot analysis, compound 94 was shown to induce expression of sfGFP in a hypoxia-dependent manner. This work represents a proof-of-concept system for hypoxia- activated small molecule-induced gene expression.